Opportunities and benefits of local content requirement policy: case of Eastern Siberian oil and gas industry - Irina Semykina (European Regional Science Association (ERSA), 2015)
This paper explores the regional economic impact of mineral resource endowment and offers specific inputs to the debate on the local content requirement (LCR) policy, gaining urgency in modern economic and political environment. Focusing on the experience of the Eastern Siberia the paper examines the way national companies operate in the newly developing oil and gas provinces of Russia. The analysis of key economic indices shows that the existing approach based on rent-seeking strategy doesn?t allow having any significant benefits from resource endowment in the regions. The key idea is that the establishment of completely new industry has to affect regional economic development, budget revenues dynamics, and employment, to influence the related industries and services in the region. Such benefits are of great importance especially for the Eastern Siberian regions which had been endured the alarming depopulation and deindustrialization processes since the collapse of Soviet Union in 1991. Oil and gas production is capital intensive industry, but at the same time involves quite limited number of employees. Equipment and machinery producing industries, as well as oil and gas related services and engineering, on the contrary can be referred to the highly skilled and labor intensive sectors. Moreover linkages between oil and gas industry and other local industries can impact regional economic growth through investments and creating value added activities in equipment and materials. Nowadays Russian national oil and gas companies don?t have a clear local content strategy, it?s mainly addressed as part of the ?corporate social responsibility agenda?. The paper provides the review of the LCR policy which has been widely used in some countries with similar industry pattern like Norway, Brazil and Malaysia. The conducted analysis let to form possible scenarios and evaluate the dynamics of regional economic development depending on the scale of LCR policy. The developed approach based on statistical modeling allows assessing both direct and indirect (via intersectoral relations) effects of LCR policy. The obtained results allow to conclude that the implementation of LCR policy lead to the growth of real income per capita and the job creation in the region which give the opportunity to reverse the population decrease trend. The development of equipment and services suppliers for oil and gas industry by ripple effects can boost socio-economic development and diversify regional economics. The paper also dwells on some pitfalls and risks accompanying LCR policy and considers crucial points of introducing this kind of policy for local and federal government.
Keywords: O20; Q32; R11; R58; 330; regional economics; oil&gas resources; local content requirement policy; Siberia